Foldable flexible electronics based on few-layer graphene coated on paper composites. (15th October 2020) - Ba, Housseinou; Sutter, Christophe; Papaefthimiou, Vasiliki; Zafeiratos, Spyridon; Bahouka, Armel; Lafue, Yannick; Nguyen-Dinh, Lam; Romero, Thierry; Pham-Huu, Cuong
Abstract: In this work, we describe an eco-friendly and cost-efficient method for the production of highly dispersed few-layer graphene solution using karaya gum as bio-inspired exfoliating agent. The as-synthesized graphene aqueous solution can be easily applied on paper sheet through dip- or brush-coating thanks to the binding properties of the gum and to the functional groups on the paper surface with the graphene sheets. The as-synthesized composites display high mechanical strength and high electrical conductivity for numerous downstream applications. Electronic circuits can be designed on such graphene-paper composites either by controlling the graphene deposit or by post-laser etching with high lateral resolution. The laser beam can also be used to create local graphitization or partial etching of the conductive line in order to generate conductive areas with different resistance. The designed smart graphene paper was experimentally tested in different electronic applications, such as lightweight conductive circuit, as well as flexible keyboard which can be directly linked to a computer, thus opening up a new route for the development of daily life connected objects. Graphical abstract: Image 1